Collective Decisions and Competitive Markets - Gersbach, H.; Haller, H. (Review of Economic Studies, 2001)
In a general equilibrium model, we allow for households with several, typically heterogeneous, members; households that make (efficient) collective consumption decisions where different households may use different collective decision mechanisms; yet households that operate within a competitive market environment. The interaction of two allocation mechanisms, collective decisions and competitive markets, is investigated, with a focus on the efficiency properties and decentralization possibilities of the dual allocation mechanism.